Pengaruh Supervisi Akademik dan Budaya Organisasi terhadap Kinerja Guru Honorer SMP Negeri di kecamatan Cikarang Selatan Bekasi - Dinny Puspita Yuliarti; Eliana Sari; Nurhattati Fuad (Program Studi Manajemen Pendidikan, 2024)
Teacher performance is one of the important elements in the achievement of quality at school because the teacher is the main component in the educational system that can affect the success of educational goals. Many factors can affect the performance of teachers, among them are seen from the implementation of supervision academic and organizational culture applied in the school environment. This research aims to determine the performance of honorary teachers who are influenced by the academic supervision and culture of organizations in the subdistrict of South Cikarang. The researchers took samples using the Purposive Sampling method of 134 honorary junior high school teachers in the subdistrict of south Cikarang, Bekasi. Data was analyzed using path analysis techniques, to test the hypothesis of the academic supervision variable (X1) on the performance of teachers (Y) and the organizational culture (X2) on the teacher performance (Y), with SPSS 25. Results of the calculation of the path analysis of X1 and Y, obtained t-count = 2,893 > ttable (α=0.05) = 1,978, the result that the variable of academic supervision influences teacher performance. Then the path analysis of X2 and Y, obtained tcount= 2,962 > ttable (α=0.05) = 1,978, showing that the variables of the cultural organization influence teacher performance.